Observation of current rectification by the new bimetallic iron(iii) hydrophobe [FeIII2(LN4O6)] on Au|LB-molecule|Au devices12. Issue 40 (14th September 2018) - Weeraratne, A. D. K. Isuri; Baydoun, Habib; Shakya, Rajendra; Niklas, Jens; Xie, Lingxiao; Mao, Guangzhao; Stoian, Sebastian A.; Poluektov, Oleg G.; Verani, Cláudio N.
Abstract : A new bimetallic iron hydrophobe, [FeIII2(L N4O6 )] (1 ) forms well-defined films used for current–voltage measurements and shows unquestionable molecular rectification. Abstract : Targeting the development of stimulus-responsive molecular materials with electronic functionality, we have synthesized and studied the redox and electronic properties of a new bimetallic iron hydrophobe [FeIII2(L N4O6 )] (1 ). The new H6 L N4O6 ligand displays bicompartmental topology capable of accomodating two five-coordinate HS Fe III ions bridged by tetraaminobenzene at a close distance of ca . 8 Å. We show that the metal-based reduction processes in (1 ) proceed sequentially, as observed for electronically coupled metal centers. This species forms a well-defined Pockels-Langmuir film at the air–water interface, with collapse pressure of 32 mN m −1 . Langmuir–Blodgett monolayers were deposited on gold substrates and used to investigate current–voltage ( I – V ) measurements. This unprecedented bimetallic hydrophobe [FeIII2(L N4O6 )] (1 ) shows unquestionable molecular rectification and displays a rectification ratio RR between 2 and 15.